EVALUATION OF WASTE MANAGEMENT USING ZERO WASTE INDEX (ZWI) AND ANALYTICAL HIERARCHY PROCESS (AHP) IN DENPASAR CITY - Budhicahyanto, Moehammad
The paradigm of waste management in Indonesia is still carried out by means of collection, transportation, and disposal, using an open dumping approach at the final processing site or landfill as in Denpasar City, Bali Province, which has a Suwung Landfill. The accumulation of garbage and leachate from this landfill has polluted the surrounding mangrove forests, causing the mangrove trees to die. Therefore, it is necessary to evaluate waste management in Denpasar City, referring to regulations on waste management. The method used is in the form of a quantitative waste management system assessment by determining the Zero waste Index (ZWI) value and determining the waste management technology that is expected by the community and stakeholders to be improved by using the Analythical Hierarchy Process (AHP) calculation. The ZWI assessment is calculated based on how much waste is processed by recycling, composting, incineration or incineration, and that goes to landfill or landfill. While AHP is used to determine the choice of technology to be used. The existing calculation is assisted by the Denpasar City waste material flow to see the flow and how much waste has been successfully processed. Then a projection is made in 2025 which refers to Presidential Regulation No. 97 of 2017 to develop a waste management scenario based on three conditions, namely pessimistic, moderate, and optimistic with the operation or without operation of Waste Processing into Electrical Energy (PSEL). The result of the ZWI value for the existing condition is 0.03 so that only 3% of waste can be converted into resources (virgin material). The scenario conditions obtained are pessimistic at 0.01; moderate at 0.03; and optimistic at 0.20. The results of data processing using AHP obtained that recycling technology is a technology that stakeholders expect to improve in Denpasar City where environmental aspects and growing concern for the community are taken into consideration.